2016
DOI: 10.1158/2326-6066.cir-15-0173
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between 4-1BB and TLR1–TLR2 Signaling in CD8+ T Cells Regulates TLR2′s Costimulatory Effects

Abstract: The activation of TLR-MyD88 (Toll-like receptor- Myeloid differentiation factor 88) signaling within T cells functions as a potent costimulatory signal that boosts antitumor and antiviral responses. However, the molecular mechanisms underlying the costimulatory processes are poorly understood. We compared microarray gene analysis data between TLR1–TLR2 stimulated and unstimulated T-cell receptor transgenic ‘pmel’ and MyD88−/− pmel CD8+ T cells and identified changes in the expression of several TNF family memb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Changes in the expression of 89 surface proteins were identified comparing the fold change between vector control and CD8α:MyD88 or CD8α:ΔIC T cells (Figure 2F). CD8α:MyD88 increased expression of IL-2 receptor chains CD25 and CD132, co-stimulatory molecules involved in T cell proliferation and cytolytic function such as CD71, CD26, and CD137 (4-1BB)(14), and various activation-associated adhesion molecules including CD44 and CD69. CD8α:MyD88 also decreased the expression of co-inhibitory molecules including CD160, CD73, Tim3, and CD39 (Figure 2F).…”
Section: Resultsmentioning
confidence: 99%
“…Changes in the expression of 89 surface proteins were identified comparing the fold change between vector control and CD8α:MyD88 or CD8α:ΔIC T cells (Figure 2F). CD8α:MyD88 increased expression of IL-2 receptor chains CD25 and CD132, co-stimulatory molecules involved in T cell proliferation and cytolytic function such as CD71, CD26, and CD137 (4-1BB)(14), and various activation-associated adhesion molecules including CD44 and CD69. CD8α:MyD88 also decreased the expression of co-inhibitory molecules including CD160, CD73, Tim3, and CD39 (Figure 2F).…”
Section: Resultsmentioning
confidence: 99%
“…As such, TLR2 might be better suited for use in a therapeutic setting, especially in situations where antigen levels and T cell functionality are limited, such as in cancer. Indeed, in a murine melanoma model, TLR2 stimulation enhanced tumor‐specific T cell responses to weakly immunogenic tumor antigens 120 and delayed tumor outgrowth in a B16‐OVA melanoma model 26,29 …”
Section: Exploiting Tlr Sensing In T Cells To Circumvent Tumor Immunementioning
confidence: 99%
“…22,23 Recently, it was shown that TLR stimulation can also function in a costimulatory fashion to enhance TCR triggering (Table 1). Combined TCR and TLR triggering enhances the activation, proliferation, memory formation and effector function of murine and human CD4 + and CD8 + T cells, 10,13,14,16,19,[24][25][26][27][28][29][30] enhancing the production of the pro-inflammatory cytokines IFN-γ, TNF-α and IL-2. 10,14,16,19,[24][25][26][28][29][30][31][32][33] Furthermore, similar to CD28, 22,23 TLR triggering also lowers the antigen threshold required for TCR triggering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, stimulation of T cells with TLR2 ligands enhances T-cell proliferation and cytokine production when they are co-stimulated via the TCR ( Komai-Koma et al, 2004;Cottalorda et al, 2006), modulates the suppressive functions of CD4 + CD25 + regulatory T cells (Sutmuller et al, 2006;Liu et al, 2006), and promotes Th17 responses (Reynolds et al, 2010). Furthermore, TLR2-induced functional activation of T cells has been shown to be critical for the induction of inflammatory diseases and protective immunity to pathogens and tumor in vivo (Reynolds et al, 2010;Geng et al, 2010;Quigley et al, 2009;Asprodites et al, 2008;Chodisetti et al, 2015;Joseph et al, 2016). We have shown that TLR2 ligands directly trigger Th1 effector functions, including interferon-g (IFN-g) production, cell proliferation, and cell survival without requiring TCR co-stimulation.…”
Section: Introductionmentioning
confidence: 99%